A modern view of the causes and mechanisms of the development of acute disseminated peritonitis - Benedyct, V.; Prodan, A.; Bahrii, V.; Dzhyvak, V. (Journal of Education, Health and Sport, 2022)
Despite the fact that the diagnosis of acute peritonitis has improved in recent years, a wide range of antibiotics is available, and minimally invasive methods of surgical treatment have been implemented, the mortality rate for this disease is high and ranges from 12.5 % to 39.2 %. The purpose of the work was to analyze data from literary sources regarding the classification of acute peritonitis, to summarize the causes and mechanisms of its development among the adult population. Analytical and bibliosemantic research methods were used in the work. It is known that according to the nature of penetration of microflora into the abdominal cavity, peritonitis is divided into primary, secondary and tertiary. According to the clinical course, peritonitis is divided into acute, subacute and chronic. According to the nature of the exudate in the abdominal cavity, serous, serous-purulent, fibrinous, fibrinous-purulent, purulent, hemorrhagic, fecal and purulent peritonitis are distinguished. To date, the existing classifications are constantly being improved and have both practical and academic significance. It has long been known that the cause of unsatisfactory results of surgical treatment of patients with acute disseminated peritonitis can be the development of intra-abdominal hypertension with subsequent development of compartment syndrome and multiple organ failure. The development of multiple organ failure is the leading cause of death in patients with acute surgical pathology. Abdominal compartment syndrome plays a big role in this, the mortality in which reaches very significant figures – 42-68 % and without treatment approaches 100 %. Therefore, the development of acute peritonitis is due to numerous reasons (in particular, acute destructive appendicitis, cholecystitis, perforated ulcer of the stomach or duodenum, intestinal obstruction, tumor processes, gynecological pathology, abdominal injuries, etc.), which in turn causes the absence of a generally recognized justified classification.